Deep anterior lamellar keratoplasty following thermokeratoplasty assisted epikeratophkia: A novel two-stage one-graft method to treat acute corneal hydrops - Liu, Chunyu; Huang, Xinyu; Shen, Jiaqi; Zhang, Yushan; Zhang, Li; Bi, Yanlong (Frontiers in Medicine, 2023)
Purpose To evaluate the clinical effects of deep anterior lamellar keratoplasty (DALK) using a single graft after thermokeratoplasty assisted epikeratophakia for the treatment of acute corneal hydrops. Methods This novel surgical procedure was performed on seven eyes of seven patients between 2019 and 2020. The procedure combines a first-stage surgery of thermokeratoplasty assisted epikeratophkia with intracameral sterile air injection and a second-stage surgery of DALK using the same corneal graft for both procedures. Main outcome measures included pre- and postoperative corrected distance visual acuity (CDVA) and anterior segment optical coherence tomography (AS-OCT) parameters. Corneal transparency, epithelization, and the presence of neovascularization, were evaluated at the 1-year follow-up visit. Results Corneal edema resolved rapidly in six of the seven cases. The mean central corneal thickness was significantly reduced from baseline to 1 day, 1 week, 1 month, and 2 months after the first-stage surgery (P < 0.0001). At a mean of 2.1 ± 0.7 months after the first-stage surgery, DALK was successfully performed in all cases. Six months later, the mean central corneal thickness was 611 ± 31 μm and the mean thickness of the recipient’s residual stroma bed was 20 ± 6 μm at the central corneal area. Mean LogMAR CDVA improved from 1.74 ± 0.34 at baseline to 0.20 ± 0.11 after DALK (P < 0.0001). No postoperative complications appeared in our case series during the 1-year observation period. Conclusion Very good visual results were obtained with a novel technique (thermokeratoplasty assisted epikeratophakia followed by DALK using the same corneal graft) in the treatment of acute corneal hydrops.